Room temperature terahertz detection by rectifying field effect transistors - Preu, Sascha; Regensburger, Stefan; Lu, Hong; Gossard, A. C. (8th German Microwave Conference, GeMiC 2014, 2019)
Rectifying field effect transistors have become versatile Terahertz detectors. We will discuss the detection mechanism. The state of the art in rectifying field effect transistors will be reviewed, showing that this novel detector concept is already comparable to well developed Schottky diode technology. The paper will discuss advantages and disadvantages of III-V materials vs. Si-based transistors. We report on ultrafast direct detection with large area GaAs-based field effect transistors at room temperature.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Field effect transistor; Rectification; THz detection